Heat stress of cattle from embryonic phase until culling - Baccouri, Wissem; Mikó, Edit; Komlósi, István (Acta Agraria Debreceniensis, 2023)
Heat stress becomes a serious problem in the livestock sector as it affects cows’ performance negatively. The objective of this paper review is to investigate the effects of heat stress during the different phases of the life cycle of cows; embryos, calves, heifers, and cows. Heat stress during early maternal gestation affects the ability of embryos to develop increasing the risk of abortion and early embryonic death. Heat stress during late maternal gestation affects the performance of calves and heifers later in their life, as it reduces growth performance, conducts physiological changes, impaired immunity, changes the behavior, and reduces the length and intensity of the estrus in heifers with decreasing in milk production in the first lactation. On the level of cows, milk quality and production, meat quality, and the final body weight decrease under hot temperatures. Heat stress decreases the conception rate, alters follicle growth, and estrous symptoms. Hormones secretion and physiological changes because of the heat stress conduct to impair the immunity system, and in oxidative stress and death in some cases. Same as for calves and heifers a change in the behavior of cows was detected in order to decrease their temperature.